(untitled) (Hekima Review, 2005)
“Au-dela de la souffrance” which literally can be translated as “beyond suffering” is the first book written by Fr. Ghislain Tshikendwa Matadi, SJ. It presents the unique and unforgettable testimony of his sick friend. This person was confronted with suffering caused by a car accident that results in her confinement in a hospital. It is true that the face of suffering and death can lead one to experience the “limitsituation” of one’s life. This biographical text shows just how in the face of suffering one can be disarmed; one’s whole life may seem to not have any meaning. But, in the very centre of that same life, one can also experience grace and the love of Godwho identified with suffering in order to save humankind. In times of weakness and suffering, the human being can encounter God and find in Him the meaning of life and even of suffering. The sick may accept in their heart the hope and the love of the One who loves and suffers first, unreservedly, in order to redeem humanity.